CMBlock: In-Browser Detection and Prevention Cryptojacking Tool Using Blacklist and Behavior-Based Detection Method - Razali, Muhammad Amirrudin; Mohd Shariff, Shafiza (Advances in Visual Informatics, 2019)
As cryptocurrency fast becoming a popular digital currency, implementation of mining script in browser-based JavaScript has become a worthwhile alternative to the traditional way of mining cryptocurrency. Based on this implementation, a new form of threat, widely called cryptojacking, has become popular on the web. A website that has been affected by cryptojacking abuses its visitor’s computing resources to mine cryptocurrency without the machine owner’s consent. This paper introduces CMBlock, a web extension for browser we have developed that can detect mining script that runs in the website. This application will be using two different kinds of approach: mining behaviour and blacklist detection technique to mitigate the cryptojacking attack. By implementing the mining behaviour detection, the application is capable of detecting unknown domain that not been listed in the blacklist. This application would be an enhancement of current countermeasure in mitigating the cryptojacking attack.